ANALISIS PROSES INOVASI APLIKASI TELUNJUK SAKTI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN WONOGIRI - Gary Rahmadhan, Oktavian; Rina Herawati, Augustin; Purnaweni, Hartuti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Problems are still often encountered in public services, such as long and complicated services. Innovation is one solution that the government can implement. Currently, there are many application innovations being created by the government, one of which is the Telunjuk Sakti application innovation at the Wonogiri Regency Population and Civil Registration Service. The implementation of the Telunjuk Sakti application has experienced a drastic decline in terms of the number of application users. Therefore, this research aims to analyze the innovation process and the driving factors that inhibit the application of Telunjuk Sakti at the Population and Registration Service of Wonogiri Regency. The theory used is the Lifecycle Innovation Theory according to the OECD which describes and describes in more depth the stages carried out in the creation of an innovation. This research uses a qualitative descriptive method with data collection using interview, observation, and documentation techniques. The results of the research show that the Population and Civil Registration Service of Wonogiri Regency applies all stages of the innovation process according to the OECD in creating the Tunjung Sakti innovation starting from Problem Identification, Idea Creation, Proposal Making, Innovation Implementation, Innovation Evaluation, Innovation Dissemination. Based on the stages that have been implemented at the Wonogiri Regency Population and Civil Registration Service, only the implementation and evaluation functions are still not optimal, while the other stages have been implemented well. The supporting factors in the innovation process of the Telunjuk Sakti application at the Wonogiri Dukcapil Office are human capital, leadership capital and organizational structure capital, while the inhibiting factors are the political environment and the environment outside the public sector. Thus, cooperation with the private sector is needed in terms of internet access and public awareness and participation is needed in using the Telunjuk Sakti application.